Aplicação das melhores práticas para apoiar a tomada de decisões em período de crise financeira: estudo de caso em empresas do setor químico e do setor financeiro - Carvalho, Tiago Vieira de (2014)
It began in 2008 a severe financial crisis that forced several industries to dramatically review their planning and decision-making processes. There are several methods to support decision-making, from methodologies as Business Process Management to the use of information systems as a Business Intelligence architecture. However, it is not enough just to have decision-making processes, it is important to use the best practices to get the best performance, either of the methodology or of the information system used. Among the best practices available, proper communication, information quality and corporate support are of great importance and influence in the corporate scenario. The objective of this work was to verify the results of the best practices application to support decision-making processes during financial crisis period on a company from chemical sector and other from financial sector. Multiple case study which included a questionnaire application in a chemical company and a action search in a financial company was held. It was concluded that the best practices application is relevant in both sectors studied, but in different ways where culture, nationality and company size proved to be influencers of the way that the best practices application occurred.